Implementation of Extreme Programming in the Asoka Makassar Integrated Early Childhood Education E-Book Activities - Awaliah, Neneng; Andryanto Aman; Nur Mustika; Erwin Gatot Amiruddin; Made Nuryani (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
Early childhood education is a critical phase that requires the attention of parents and the continued responsibility of teachers within early childhood education institutions (PAUD). One of the primary philosophies in early childhood education includes shaping, honing, loving, and fostering. Fostering refers to efforts aimed at developing a child's personality and identity, ensuring they possess essential qualities such as integrity, faith, and piety. This research aims to monitor children's activities at PAUD Asoka Makassar through the development of an electronic activity book, commonly known as an e-book of activities. The system manages school activities and monitors student progress, implemented using the Extreme Programming (XP) methodology and Visual Studio Code as the code editor. The implementation of this system facilitates the monitoring of children's activities by both schools and parents, thereby enhancing the overall quality of education at the institution. This research contributes to the knowledge base by demonstrating the practical application of XP in educational settings, providing insights for future studies on digital monitoring systems in early childhood education.